Scavenging and metal chelating potential of Carthamus tinctorius L. extracts - Dehariya, Rashmi; Chandrakar, Jagriti; Dubey, Satish; Ojha, Kundan; Dixit, Ashwini Kumar (Current Botany, 2020)
Carthamus tinctorius leaves were extracted with methanol and distilled water. The extracts were evaluated for their potential free radical scavenging capacity using four different in vitro methods (DPPH, metal chelation, radical removal and hydrogen peroxide scavenging methods). The total phenolic content obtained for aqueous (112. 2±1.708 GAE mg/g) and for methanolic extract (89.66±2.00 GAE mg/g). In DPPH, IC50 values was found to be 176.66±2.08 and 278.33±1.52 and 310.33±1.52 for the ascorbic acid, aqueous and methanolic extract respectively. In superoxide radical scavenging IC50 values are 381.27±1.43, 544.42±2 and 606.78±3.02 µg/ml for the ascorbic acid, aqueous and methanolic extract respectively. In the metal chelating activity, IC50 values are 385.94±3.00, 337±1 and 487±0.984 µg/ml for the EDTA, aqueous extract and methanolic extract respectively. In hydrogen peroxide scavenging, IC50 values were 261±1, 278±3.52 and 370±1 µg/ml for the ascorbic acid, aqueous extract and methanolic leaf extract of Carthamus tinctorius respectively. The correlation suggests that phenolic compounds are responsible for the antioxidant activities of leaves.